(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Questions: Which new plants for the Podolian flora (Ukraine) were discovered? Which plants were mistakenly cited in the flora of Podolia? Location: Podolian Upland, Ukraine. Materials and methods: field studies (were conducted during 2007–2023), morphological identification of plants, analysis of data sources. Nomenclature: POWO 2024, Kuzemko et al. 2018. Results: The results of floristic research on the territory of Podolia are presented. The greatest number of new findings of native plants were concentrated in three natural areas of Eastern Podolia: along the Dniester River valley, in the south of Middle Pobuzhzhia (including the Savran sands area) and in the territory of Prybuzhske Polyssia. The native slopes of the Dniester River valley play an essential role in the preserving habitats and natural migrations of plants. For the first time, 11 new plant species were discovered in this ecocorridor in the south of Vinnytsia Region, in particular, Ephedra distachya, Lactuca viminea, Onobrychis gracilis, etc. The distribution of Quercus pubescens at the northern border of the range in the Vinnytsia Region has been specified in detail. Some features of the adventitization of the flora of Podolia, which mainly occurs somewhat more slowly than in other regions, are noted. On the basis of a critical study of the flora, 10 taxa were considered, which for various reasons were erroneously cited for the territory of Podolia, in particular: Hylotelephium telephium, Symphytum orientale, etc. Conclusions: New locations of 84 species and subspecies of wild plants were discovered, including 58 native and 26 alien (16 ergasio-phygophytes and 10 xenophytes). For the first time, 11 plant species were discovered in the flora of Podolia (Gypsophila perfoliata, Lotus stepposus, Polygonum novoascanicum, Viola hymettia, etc.). 30 new species for the flora of the Vinnytsia, 8 new species for the flora of the Mykolaiv, 4 new species for the flora of the Odesa and 2 new species for the flora of the Kirovohrad regions were identified. Within the administrative regions, it is still relevant to carry out an inventory of flora, particularly, for Vinnytsia Region, the flora of which, according to a preliminary assessment, covers more than 1,750 wild plants.